The gut microbiota in infants of obese mothers increases inflammation and susceptibility to NAFLD. Issue 1 (December 2018) - Soderborg, Taylor; Clark, Sarah; Mulligan, Christopher; Janssen, Rachel; Babcock, Lyndsey; Ir, Diana; Lemas, Dominick; Johnson, Linda; Weir, Tiffany; Lenz, Laurel; Frank, Daniel; Hernandez, Teri; et al.
Abstract Maternal obesity is associated with increased risk for offspring obesity and non-alcoholic fatty liver disease (NAFLD), but the causal drivers of this association are unclear. Early colonization of the infant gut by microbes plays a critical role in establishing immunity and metabolic function. Here, we compare germ-free mice colonized with stool microbes (MB) from 2-week-old infants born to obese (Inf-ObMB) or normal-weight (Inf-NWMB) mothers. Inf-ObMB-colonized mice demonstrate increased hepatic gene expression for endoplasmic reticulum stress and innate immunity together with histological signs of periportal inflammation, a histological pattern more commonly reported in pediatric cases of NAFLD. Inf-ObMB mice show increased intestinal permeability, reduced macrophage phagocytosis, and dampened cytokine production suggestive of impaired macrophage function. Furthermore, exposure to a Western-style diet in Inf-ObMB mice promotes excess weight gain and accelerates NAFLD. Overall, these results provide functional evidence supporting a causative role of maternal obesity-associated infant dysbiosis in childhood obesity and NAFLD. Infants born to obese mothers have altered microbiome and increased risk of obesity and NAFLD. Here the authors establish causality by showing that maternal obesity-shaped infant gut microbiome induces macrophage dysfunction, inflammation, and diet-induced metabolic disease in germ-free mice.